THE EVOLUTION OF A JUMPING-SHEET - Sergey M. Dymov; Maxim V. Vishchekin; Aleksandr M. Aleksandrov; Dmitry Yu. Rusanov (Актуальные вопросы пожарной безопасности)
The article discusses changes in the design of the jumping-sheet from the 19th century to the present. The main positive and negative design features of the jumping-sheet are determined. The calculation of the efforts that arise on the hands of firefighters when a person falls on a jumping-sheet is made. The descriptions of the most common and promising models of jumping-sheet are given.